Developing English Materials with Religious Content for Students of State Hindu University of I Gusti Bagus Sugriwa Denpasar - Made Wahyu Mahendra; Made Yudiantara Risadi (ELLITE, 2022)
Contextual and integrated teaching and learning is one of the most important issues to discuss in the respect of educating students with particular social background. This empowers students to actively learn a subject because the material provided is close to their daily lives while being integrated to other subject. This study aims to develop an English teaching material integrated with Hindus religious values for students of State Hindu University of I Gusti Bagus Sugriwa Denpasar, employing a Research and Development design by adopting the ADDIE model. Further, students are expected to not only improve their English skills, but also strengthen their religious values. The analysis phase includes needs analysis by examining the current syllabus, observing the teaching in classroom, and interviewing students. During the design process, the product is decided to be in a form of e-module integrating religious values. Development process focuses on the validity test of the product and also field tryout to examine the product’s practicality and usability. The validity test involves five experts on content, layout, and display of the product where all components resulted in valid category. The result on the field tryout toward small group also reveal that the content aspect get 717 points (78%) and categorized as good, the layout aspect get 620 points (77%) and categorized as good, and language aspect get 435 (75%) and being categorized as good. The result of this study is expected to provide lecturers with options in teaching English as compulsory subject in higher Education.